Study on The Influence of Corridor 4 Feeder Transportation on Light Rail Transit (LRT) Passenger Demand in Palembang City TOD-based - Sarwandy, M. Hijrah Agung; Royan, Noto; Jaya, Meldo Andi; Sulfiani, Mega (Riwayat: Educational Journal of History and Humanities, 2025)
The existence of LRT feeder transportation in Palembang City is felt to be very helpful for the community in traveling both from home to work, shopping centers, and other public service centers. Moreover, the Palembang part of Ulu is a developing and densely populated area. Corridor 4 feeders of the LRT are included in the station area which has different characteristics in land use and building density. Polresta Station is included in the TOD Neighbourhood Medium Density typology (Jaya, M.A., Sary, R.K., Ramdhani, M.I. (2020). The purpose of this study is to evaluate the influence of Corridor 4 feeder transportation on the demand for Light Rail Transit (LRT) passengers in Palembang City based on Transit Oriented Development (TOD). The research data was obtained from surveys and load factor analysis. This study uses a quantitative approach, using regression and correlation analysis techniques. The results show that various variables, such as distance, travel time, and type of transportation, have a significant influence on the demand of LRT passengers.